PUBLIC OPINION IN ADDRESSING THE CONFLICT OF PT. RAPP IN PULAU PADANG, DISTRICT MERANTI SUBDISTRICT MERBAU - AHMAD TARMIZI; RUSMADI AWZA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
PT. RAPP (PT Riau Andalan Pulp and Paper) is a company thatmanufactures pulp and have a timber plantations to create a seamless qualitypaper, which has now crossed in the Pulau Padang, district Meranti, subdistrictmerbau. So that has led to conflicts between people and PT RAPP. The conflictbegan from December of 2009 until now there is no way the solution of the localgovernment. People has been assumed that if the ongoing forest cultivation by PT.RAPP in Pulau Padang , will likely hamper the needs of forest products that havebeen used for decades by the people who inhabit the island. This study aims todetermine how the public opinion against the conflict of PT RAPP in PulauPadang, subdistrict merbau district Meranti, as well as the factors that influencethe formation of public opinion against the conflict of PT RAPP in Pulau Padang.This study used qualitative methods of data collection were obtained basedon the fact that occurs through observation and interviews. Informants in thisstudy amounted to 12 people, consisting of (headman, society, chairman of RiauFarmers Union (STR), Public figures and Public Relations of PT RAPP). Dataanalysis techniques used in this research is to use interactive data analysis modelof Hubermen and Miles, using the technique of checking the validity of the data istriangulation techniques and extension participation.From the results of the study showed that public opinion against theconflict of PT RAPP in Pulau Padang subdistricts merbau district meranti is verydetrimental to people in the area. people of Pulau Padang would still reject theentry of PT RAPP (Riau Andalan Puld & Paper) in Pulau Padang, because thecompany is considered to take public land. The forest in Pulau Padang is anexpanse of peat and most of the people are very dependent on the forest productsin the regionKeyword : Opinion, Communication, Conflict